COMPOSITION OF ADMINISTRATIVE OFFENSE WITH A REFERENCE (BLANKET) METHOD OF PRESENTATION: REQUIREMENTS FOR CONTENT AND STRUCTURE - Kunev, Yuriy (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to formulate proposals regarding the content and structure of protective and regulatory norms to which the protective provision with a reference (blanket) disposition refers. Research methods: systemic analysis and synthesis, comparative legal and doctrinal knowledge of administrative legislation; methods of comparison and comparison of the provisions of international and national legislation, as well as the method of generalization and modeling of new theoretical knowledge. Results: problems of further development of administrative regulation of administrative offenses are identified and specific ways of solving them are proposed. The properties of administrative legislation are determined by the quality of the general legal norm in conjunction with the regulatory and protective components. The main problems in the field of protection of regulatory norms are that the regulatory norm must be a specifically defined part of the disposition of the protective norm. For a systematic solution of problems with the content of administrative security norms, it is necessary to link security norms to regulatory norms and to present the components of offenses in accordance with a system of standardized requirements. Discussion: the provision is argued that it is necessary to check all existing components of administrative offenses for compliance of the content of the activity model of related legal and regulatory norms with the requirements for their structure and content formulated in the conclusions of the article.